Tolerance of Transplastomic Tobacco Plants Overexpressing a Theta Class Glutathione Transferase to Abiotic and Oxidative Stresses - Stavridou, Evangelia; Michailidis, Michail; Gedeon, Stella; Ioakeim, Antri; Kostas, Stefanos; Chronopoulou, Evangelia; Labrou, Nikolaos E.; Edwards, Robert; Day, Anil; Nianiou-Obeidat, Irini; Madesis, Panagiotis (Frontiers in Plant Science, 2019)
Chloroplasts are organelles subjected to extreme oxidative stress conditions. Biomolecules produced in the chloroplasts act as signals guiding plant metabolism towards stress tolerance and play a major role in regulating gene expression in the nucleus. Herein, we used transplastomic plants as an alternative approach to the expression of transgenes in the nucleus for conferring stress tolerance to abiotic stresses and herbicides. To investigate the morphophysiological and molecular mechanisms and the role of plastid expressed GSTs in tobacco stress detoxification and stress tolerance, we used transplastomic tobacco lines overexpressing a theta class glutathione transferase (GST) in chloroplasts. The transplastomic plants were tested under drought (0, 100 and 200 mM mannitol) and salinity (0, 150 and 300 mM NaCl) in vitro and under herbicide stress (Diquat). Our results suggest that ptAtGSTT lines were tolerant to oxidative and salinity stresses and showed enhanced response tolerance to mannitol-induced osmotic stress compared to WT plants. Overexpression of the Arabidopsis thaliana AtGSTT in the chloroplasts resulted in enhanced photo-tolerance and turgor maintenance under stress. Whole-genome transcriptome analysis revealed that genes related to stress tolerance were upregulated in ptAtGSTT2a line under both control and high mannitol stress conditions. Transplastomic plants overexpressing the ptAtGSTT2a in the chloroplast showed a state of acclimation to stress, as only limited number of genes were upregulated in the ptAtGSTT2a transplastomic line compared to WT under stress conditions while at the same time genes related to stress tolerance were upregulated in ptAtGSTT2a plants compared to WT in stress-free conditions. In parallel, the metabolic profile indicated limited perturbations of the metabolic homeostasis in the transplastomic lines and greater accumulation of mannitol and soluble sugars under high mannitol stress. Therefore, transplastomic lines seem to be in a state of acclimation to stress under stress-free conditions, which was maintained even under high mannitol stress. The results help to elucidate the role of GSTs in plant abiotic stress tolerance and the underlying mechanisms of the GSTs expressed in the chloroplast, towards environmental resilience of cultivated crops.